Kesalahan Berbahasa Tataran Sintaksis Bidang Kalimat pada Komentar Youtube Najwa Shihab Melawan Corona - Wenty Agustin; M. Nur Mustafa; Elvrin Septyanti (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
This study aims to identify and describe the form of language errors at the syntactic level in the sentence field in the Youtube commentary of Najwa Shihab Melawan Corona. This type of research is qualitative or can be interpreted as research that emphasizes the quality of data collected using descriptive methods. Sources of data in this study are comments written by YouTube users on the Najwa Shihab Melawan Corona broadcast. The data in this study are writings that represent the opinions of Youtube users regarding related videos. The data collection techniques used in this study were reading and note-taking techniques. The data analysis technique used in this study was data reduction, data presentation, and conclusion drawing. The results of this study found language errors in the sentence field in the form of non-subjected sentences, non-predicated sentences, lucky sentences, duplication of subjects, illogical sentences, ambiguity sentences, conjunction omissions, Excessive use of conjunctions, unparalleled sequences, use of foreign terms and use of unnecessary question words.